2018
DOI: 10.20944/preprints201811.0483.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Suppression of IFN-g Production in Murine Splenocytes by Histamine Receptor Antagonists

Abstract: Accumulating evidence suggests that histamine synthesis induced in several types of tumor tissues should modulate tumor immunity. We found that a transient histamine synthesis was induced in CD11b+Gr-1+splenocytes derived from BALB/c mice transplanted with a syngeneic colon carcinoma, CT-26, when they were co-cultured with CT-26 cells. Significant levels of IFN-γ were produced under this co-culture condition. We explored the modulatory roles of histamine on IFN-γ production and found that s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Another study also reported that cimetidine did not influence the IFN-c production, as seen in this study. From each histamine receptor antagonist, only H1R and histamine-4 receptor antagonist were shown to decrease IFN-c production [25].…”
Section: Changes In Serum Ifn-c Levelmentioning
confidence: 96%
“…Another study also reported that cimetidine did not influence the IFN-c production, as seen in this study. From each histamine receptor antagonist, only H1R and histamine-4 receptor antagonist were shown to decrease IFN-c production [25].…”
Section: Changes In Serum Ifn-c Levelmentioning
confidence: 96%